Why do nulliparous teenagers have the highest rate of unassisted vaginal deliveries compared to their older counterparts? - Pierre-Yves Robillard; Silvia Iacobelli; Malik Boukerrou; Brahim Boumahni; Francesco Bonsante; Phuong Lien Tran; Gustaaf Dekker (The Journal of Maternal-Fetal & Neonatal Medicine)
Objectives To establish why teenagers (13–19 years old) primiparas have higher rates of unassisted vaginal deliveries compared with their older counterparts.Methods University’s maternity, 24.5-year-observational population-based cohort study (2001–2024). All consecutive nulliparous singleton pregnancies. Analysis of the main indications for cesarean sections (c-sections) and also need for operative vaginal procedures of all nulliparous pregnant women with an age range from 14 to 40+ yrs.Results Out of 33,785 singleton primiparous livebirth pregnancies, vaginal births represented 91% at the ages 14–15 dropping to just 55% at ≥40 yrs. The rate of c-sections was 9% at the ages 14–15, increasing to a rate of 45% at ≥40 years. Operative vaginal delivery rate was 12.1% at the ages 14–15 years, versus 29.8% at ≥ t 40 years (both χ2 for trend, p < .0001). Two-thirds of the indications for c-sections were “abnormal fetal monitoring” (AFM) and “Obstructed Labor” (OL). The indication AFM had a χ2 for a negative linear trend p = .0004: a high rate of 39% for the ages 14–15, and 25% for the ages over 40 years. The indication OL had a positive trend with maternal ages but not linear (p = .13): 17% for the ages 14–15 years, 25% for the ages 16–19, followed by a plateau around 32% between 20 and 40 years.Conclusions Vaginal births in primiparas without obstetrical assistance occur preferably at younger ages with a regular negative linear trend, p < .001 until the ages 40+. The indication AFM for c-sections also had a negative linear trend, p = .0004, while OL as indication for c-sections represented a minority in teenagers (below breech presentation). In teenagers, the higher rate of unassisted vaginal births may be due to an intrinsic biologic cause (uterine contractility).